Question: Quadratic Formula

May 2010
22
0
I keep making some type of mistake on this problem, can someone please show how to work it out? I think maybe I get the signs mixed up. I am supposed to work it using the quadratic formula.

s^2 = 9 + s(1-2s)

Thanks!!
 

pickslides

MHF Helper
Sep 2008
5,237
1,625
Melbourne
\(\displaystyle s^2 = 9 + s(1-2s)\)

\(\displaystyle s^2 = 9 + s-2s^2\)

\(\displaystyle 3s^2 -s- 9 =0\)

\(\displaystyle
s = \frac{-(-1)\pm\sqrt{(-1)^2-4\times 3 \times -9}}{2\times 3}=\dots
\)

can you finish it?
 
  • Like
Reactions: dwatkins741
May 2010
22
0
Now I get it

I wasn't distributing the s before using the quadratic formula. Thanks so much!!